The Impact of Technological Development on the Growth of the Manufacturing Sector in Kingdom of Saudi Arabia (1995-2022) - Nasrulddin, Vivian; Alzahrani, Rawan (The Arab Journal of Administration, 2025)
The objective of this study was to identify the impact of technological development on the growth of the manufacturing sector in the KSA during the period (1995-2022), and in order to discover the aspects of the relationships between the variables, a Multiple Linear Regression Analysis model was used, and a number of tests to express the relationship between growth in the manufacturing sector as a dependent variable, and the related independent variables, which were selected based on previous studies and the researcher’s judgments, represented in: spending on technological development, labor force, number of factories, and the value of manufacturing exports.By testing the hypotheses that were identified, the general trend of the variables was identified through the statistical program E-views. As expected, the results showed a direct relationship between the dependent variable and both the value of manufacturing exports and spending on technological development, while the results showed -contrary to what was expected- a direct relationship between the dependent variable and both the labor force and the number of factories. The study recommends a number of recommendations, It is represented in making awareness efforts for small and medium-sized enterprises in the process of selecting the appropriate technological technology in the production process, which enhances the efficiency of the outputs, providing the appropriate environment for investors in the technological field and the industrial field to achieve a competitive advantage over the rest of the industrialized countries, paying attention to manufacturing industries and their exports to reduce dependence on Oil revenues, conducting more studies related to technological development and its impact on the industrial sector in the KSA.